Dynamic adsorption of diclofenac onto a magnetic nanocomposite in a continuous stirred-tank reactor. (15th October 2022) - Rocha, L.; Sousa, E.M.L.; Gil, M.V.; Otero, M.; Esteves, V.I.; Calisto, V.
Abstract: In this study, a waste-based magnetic activated carbon (MAC) was used for the first time in a continuous-flow stirred tank reactor (CSTR). The aim was to evaluate the dynamic removal of diclofenac (DCF) from water and wastewater. Firstly, the breakthrough curves corresponding to DCF adsorption from distilled water at different feed flow rates and doses of MAC were determined. After selecting the most favourable conditions, namely 0.18 h L −1 flow rate and 400 mg L −1 of MAC, the effect of different aqueous matrices was studied, with the breakthrough curves evidencing a performance decline in wastewater in comparison with distilled water. Finally, the exhausted MAC was magnetically recovered, regenerated by microwave-assisted heating and applied in two subsequent adsorption cycles. The regeneration studies pointed to a decrease of the specific surface area and an improvement of the magnetic retrievability of MAC. After the first regeneration step, just mild effects were observed in the dynamic adsorptive performance of MAC. However, after a second regeneration step, the performance declined ca. 50%. Overall, the results highlight the feasibility of producing waste-based magnetic composites that simultaneously combine high adsorption efficiency under dynamic operation in a CSTR, with easy retrievability and successful one-stage regeneration for further reutilization. Graphical abstract: Image 1 Highlights: Diclofenac (DCF) adsorption by waste-based magnetic activated carbon (MAC) was aimed. Adsorptive performance was evaluated in a continuous stirred tank reactor (CSTR). Most favourable flow rate and MAC dose for DCF adsorption from water were selected. Under such conditions but from wastewater, matrix effects affected DCF adsorption. Regenerated MAC by microwave heating (1 step) kept its CSTR adsorptive performance.